Applied Mathematics exercises in a secondary grammar school lesson - Kézi, Csaba (International Journal of Engineering and Management Sciences, 2020)
In the frame of the project EFOP-3.6.1-16-2016-00022 „Debrecen Venture Catapult Program" on may, 2019, I maked a test and it was completed by a secondary grammar school students in Mátészalka. In this lesson there were many exercises that showcase the different applications of mathematics.